2020
DOI: 10.1007/s12250-020-00304-4
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus MGF360-12L Inhibits Type I Interferon Production by Blocking the Interaction of Importin α and NF-κB Signaling Pathway

Abstract: African swine fever (ASF) is an infectious transboundary disease of domestic pigs and wild boar and spreading throughout Eurasia. There is no vaccine and treatment available. Complex immune escape strategies of African swine fever virus (ASFV) are crucial factors affecting immune prevention and vaccine development. MGF360 genes have been implicated in the modulation of the IFN-I response. The molecular mechanisms contributing to innate immunity are poorly understood. In this study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 46 publications
2
63
0
Order By: Relevance
“…pA238L inhibits TNF-a generation and expression. CBP/p300 is a histone acetyltransferase (HAT) that enables histone acetylation to promote transcription factor-mediated target (76) inhibit the interaction between p65 and importin a inhibit the interaction between NF-kB andnuclear transport proteins gene transcription. pA238L replaces the combination of cyclic AMP-responsive element/k3complex with CBP/p300 on the TNF-a promoter, inhibiting TNF-a activation.…”
Section: Tnf-a Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…pA238L inhibits TNF-a generation and expression. CBP/p300 is a histone acetyltransferase (HAT) that enables histone acetylation to promote transcription factor-mediated target (76) inhibit the interaction between p65 and importin a inhibit the interaction between NF-kB andnuclear transport proteins gene transcription. pA238L replaces the combination of cyclic AMP-responsive element/k3complex with CBP/p300 on the TNF-a promoter, inhibiting TNF-a activation.…”
Section: Tnf-a Inhibitionmentioning
confidence: 99%
“…Moreover, MGF360 and MGF505/530 inhibit the I-type IFN production and impact ( 14 ). ASFV MGF360-12L reduces IFN-β and NF-κB promoters activity and inhibits mRNA transcription of IFN-β, IRF3, STING, TBK1, ISG54, ISG56 and AP-1 ( 76 ).…”
Section: Asfv Immunomodulation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that deletion of MGF360-12L led to upregulation of IFN-β and provided protective immunity against the challenge of virulent ASFV ( Reis et al, 2016 ), suggesting that MGF360-12L could be a potential IFN antagonist. To verify this hypothesis, Zhuo et al (2020) performed an in-depth study and found that MGF360-12L can suppress the transcription level and promoter activity of IFN-β and NF-κB. MGF360-12L could interact with nuclear transport proteins importin α (KPNA2, KPNA3, and KPNA4) at the nuclear localization signal domain to disrupt NF-κB nuclear translocation, resulting in the inhibition of type I IFN production.…”
Section: African Swine Fever Virus Immune Evasion Mechanisms and Their Relationship To Live Attenuated Vaccinesmentioning
confidence: 99%
“…Additionally, multiple ASFV proteins, including A276R, A528R, I329L, DP96R, MGF-505-7R, and MGF360-12L, were shown to contribute to the inhibition of IFN production by targeting different pathways (14,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%